CRISPR/Cas mediated genome-editing for rice improvement - BN, Devanna; Molla, Kutubuddin A; C, Parameswaran; Katara, Jawahar Lal; Kumar, A; Panda, R S; Kishor, J; Bandita, S; B, Cayalvizhi; Samantaray, Sanghamitra (ORYZA-An International Journal of Rice, 2021)
Rice is one of the important food crops, feeding more than 50% of the global population. The climate change isÂ adversely affecting the rice production across the rice growing regions. The major challenges posing threat toÂ the world rice production are various biotic and abiotic stresses. Rice is grown and consumed largely by theÂ developing countries, and most part of the population in these regions are undernourished with unbalancedÂ and comparatively low nutritional food. Therefore, it is of utmost importance to develop rice varieties for higherÂ nutritional value with attributes for better adaptability to various stresses. In the present review, we haveÂ discussed about the different CRISPR/Cas genome editing tools, and their applications for biotic and abioticÂ stress tolerance, yield and also for grain and nutritional quality improvement in rice.